1988
DOI: 10.1152/ajpregu.1988.254.2.r197
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal response to exercise in humans: influence of hypoxia and physical training

Abstract: Hypoxia and physical training alter the responses of glucoregulatory hormones to absolute work loads in opposite directions. These effects have tentatively been ascribed to changes in maximal O2 consumption (VO2 max) and ensuing changes in relative work loads. However, hypoxia as well as training may more specifically influence the hormonal response. We therefore differentiated the influence of hypoxia, training, and VO2 max, respectively, on the hormonal response to bicycle exercise. Responses to hypoxia in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…Furthermore, and of relevance for the differential glucocorticoid responses to stress in the exercised rats, stressors that are physically demanding such as forced swimming evoke much larger increases in adrenaline than psychological challenges such as novel cage stress which are hardly physically demanding [59,60,61,62]. As mentioned, exercised animals show an enhanced adrenaline secretory capacity and indeed higher maximal adrenaline responses to various physically demanding challenges have been observed in exercised subjects [63,64,65,66,67,68,69]. Therefore, in aggregate it may be postulated that in exercised animals an enhanced adrenaline response upon a physically demanding challenge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, and of relevance for the differential glucocorticoid responses to stress in the exercised rats, stressors that are physically demanding such as forced swimming evoke much larger increases in adrenaline than psychological challenges such as novel cage stress which are hardly physically demanding [59,60,61,62]. As mentioned, exercised animals show an enhanced adrenaline secretory capacity and indeed higher maximal adrenaline responses to various physically demanding challenges have been observed in exercised subjects [63,64,65,66,67,68,69]. Therefore, in aggregate it may be postulated that in exercised animals an enhanced adrenaline response upon a physically demanding challenge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypoxia-stimulated glucose uptake is absent in mice expressing a dominant negative mutant AMPK, but contraction-stimulated glucose uptake is only partially reduced (ϳ50%) in these mice (37). No study has examined the effect of hypoxia on skeletal muscle AMPK activity, muscle energy balance, and glucose disposal during exercise in humans.It is critical, when comparing metabolism between hypoxic and normoxic exercise, that the intensity be normalized to both the absolute and relative workload, since the maximal rate of oxygen uptake (V O 2 peak ) is reduced in hypoxia (5,28,34). In other words, when exercise is performed under hypoxic conditions at the same absolute workload (with respect to power output) as normoxic conditions, the relative intensity of exercise (with respect to V O 2 peak ) is much higher compared with normoxic conditions.…”
mentioning
confidence: 99%
“…The hormonal response to hypoxic exercise, particularly catecholamines, is largely related to the relative rather than the absolute exercise intensity (28,34). At the same absolute intensity, hypoxic exercise increases glucose uptake (5,30,43), muscle glycogen breakdown (40), and plasma and muscle lactate levels (5,28,30,34) and increases the extent of muscle energy imbalance (25,40,47). However, it is not known whether the hypoxia effect on these metabolic variables is due to the hypoxic exercise being performed at a higher relative intensity.…”
mentioning
confidence: 99%
“…The similar effects in HT and NT might also be related to the fact that the stimulation of the b-adrenergic receptors involved in oxidative adaptations to endurance training (Booth and Baldwin 1996) was identical for HT and NT during training. A previous study (Kjaer et al 1988) reported that epinephrine and norepinephrine responses to exercise were similar in untrained subjects whether the exercise was performed at the same relative work rate in hypoxia or in normoxia. Finally, if one considers heart rate as an indicator of the metabolic load for muscle tissues in exercise, it is interesting to note that HT and NT displayed the same heart rates during the training sessions (Table 2).…”
Section: Discussionmentioning
confidence: 89%